Spatial scaffold effects in event memory and imagination. Issue 4 (27th February 2018) - Robin, Jessica
Abstract : Spatial context is a defining feature of episodic memories, which are often characterized as being events occurring in specific spatiotemporal contexts. In this review, I summarize research suggesting a common neural basis for episodic and spatial memory and relate this to the role of spatial context in episodic memory. I review evidence that spatial context serves as a scaffold for episodic memory and imagination, in terms of both behavioral and neural effects demonstrating a dependence of episodic memory on spatial representations. These effects are mediated by a posterior‐medial set of neocortical regions, including the parahippocampal cortex, retrosplenial cortex, posterior cingulate cortex, precuneus, and angular gyrus, which interact with the hippocampus to represent spatial context in remembered and imagined events. I highlight questions and areas that require further research, including differentiation of hippocampal function along its long axis and subfields, and how these areas interact with the posterior‐medial network. This article is categorized under: Psychology > Memory Neuroscience > Cognition Abstract : Spatial contexts (e.g., a familiar building on campus) provide a foundation for remembered events (e.g., attending class in that building) and imagined future events (e.g., picturing one's graduation in that building). This paper reviews the behavioral and neural evidence supporting the role of spatial context in episodic memory and imagination.